Evaluasi Aplikasi Seluler KAI Access Menggunakan Metodologi Usability Testing - Riya Widayanti; Arif Apriansah; Sandy Lorent; Gideon Hatorangan Rajagukguk (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The utilization of information technology has increased the efficiency and effectiveness of business processes, particularly in the transportation sector. To facilitate users, PT. Kereta Api Indonesia (Persero) offers ticket booking services through the KAI Access smartphone application. However, this application has received considerable negative feedback regarding its usability, which jeopardizes its effectiveness, efficiency, and user experience. The purpose of this study is to evaluate the usability of the KAI Access application and identify areas needing improvement. The data collection method used is quantitative, following ISO 9241-11 standards, and involves several users to assess the three main aspects of usability: effectiveness, efficiency, and user satisfaction. The study's findings indicate that 40% of users experience difficulties in navigating and completing tasks within the application, highlighting issues with the interface design. The average time required to complete a task is 8 minutes,longer than similar applications, indicating a low level of application efficiency. User satisfaction is reflected by an average score of 3.2 out of 5, indicating a somewhat disrupted level of satisfaction. The analysis of the study results shows that the main issues lie in unclear navigation, incomplete information, unappealing visuals,and poor application performance. To improve the usability of the KAI Access application, it is recommended to make improvements in navigation design, provide clearer and more comprehensive information, refine the visual design, and optimize the application's workflow.